KAJIAN HADIS-HADIS TENTANG DAKWAH KULTURAL NAHDLATUL ULAMA DAN MUHAMMADIYAH DI SULAWESI - Muhammad Jufri (IAIN PAREPARE, 2016)
Two mass organizations that have long existed in the archipelago, including in South Sulawesi is the Nahdlatul Ulama and Muhammadiyah. Both of these mass organizations has been involved in the spread of Islam and even the pre - independence Indonesia. One thing that is unique and differentiates it from other missionary movement is preaching cultural synergy between Islam and local culture. This article examines the hadiths (the educational perspective) in view of the existence and power of preaching is done either by the Nahdlatul Ulama and Muhammadiyah. This paper other than using textual approach (hadith) also uses historical analysis critical to see more about the hadiths is justified by both organizations (Nahdlatul Ulama and Muhammadiyah) in carrying out the vision of his message.